Serum C reactive Protein in Preeclamptic Women (Journal of Bangladesh College of Physicians and Surgeons, 2014)
The incidence of preeclampsia is high in the developing countries. Since this condition is preventable if detected and treated at an early stage, it is essential to diagnose the disease at an early stage, and to institute proper medical care on time. The present study carried out in the Department of Obstetrics and Gynaecology, BIRDEM, and Dhaka Medical College Hospital during January 2009 and June 2010, was aimed to find out concentration of serum C reactive protein (CRP) in preeclamptic women. The study included 60 pregnant women; 30 normal (control) and 30 preeclamptic (case) pregnant women in their third trimester. Estimation of CRP was done by immunoprecipitation assay turbulometry method for both groups. The mean (±SD) age was 23.23±4.58 (control) and 23.90±3.20 (case) years (no significant difference). However, BMI, SBP and DBP were significantly (P